2010
DOI: 10.1186/1471-2407-10-570
|View full text |Cite
|
Sign up to set email alerts
|

Complete response in gallbladder cancer to erlotinib plus gemcitabine does not require mutation of the epidermal growth factor receptor gene: a case report

Abstract: BackgroundGallbladder cancer typically follows an aggressive course, with chemotherapy the standard of care for advanced disease; complete remissions are rarely encountered. The epidermal growth factor receptor (EGFR) is a promising therapeutic target but the activity of single agent oral EGFR tyrosine kinase inhibitors is low. There have been no previous reports of chemotherapy plus an EGFR-tyrosine kinase inhibitor (TKI) to treat gallbladder cancer or correlations of response with the mutation status of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Although response rates in clinical studies of EGFR inhibitors across various tumor types have not been sufficiently high to warrant use in unselected patients, in a similar manner to breast cancer, durable responses have been observed at low frequencies across multiple epithelial tumor types, including cutaneous squamous cell carcinoma and gallbladder cancers (Maubec et al, 2011;Mody et al, 2010). Given that EGFR is known to play a critical role in transit-amplifying populations across various normal tissues (Schneider and Yarden, 2016), further investigation is warranted to determine whether the EGFR-associated tumorigenic program we have identified plays a role in treatment response in other tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Although response rates in clinical studies of EGFR inhibitors across various tumor types have not been sufficiently high to warrant use in unselected patients, in a similar manner to breast cancer, durable responses have been observed at low frequencies across multiple epithelial tumor types, including cutaneous squamous cell carcinoma and gallbladder cancers (Maubec et al, 2011;Mody et al, 2010). Given that EGFR is known to play a critical role in transit-amplifying populations across various normal tissues (Schneider and Yarden, 2016), further investigation is warranted to determine whether the EGFR-associated tumorigenic program we have identified plays a role in treatment response in other tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…11 Genomic correlates of extraordinary response to targeted therapeutics have been demonstrated in other contexts, 12–16 raising the possibility that a rare extreme response to erlotinib hydrochloride may result from somatic alterations in a patient’s tumor.…”
mentioning
confidence: 99%
“…A variety of therapeutic trials targeting EGFR in GBC patients have been completed, but endpoints were varied. Mody et al 137 reported a metastatic GBC case who received a combination treatment with gemcitabine (1000 mg/m 2 ) on days 1 and 8 every 21 days and daily erlotinib (100 mg). The disease remained for 18 months with no progression after 12 cycles of combination therapy followed by maintenance with only erlotinib for 6 months.…”
Section: Targeted Therapy Of Gbcmentioning
confidence: 99%